(untitled) (Latakia University Journal -Biological Sciences Series, 2021)
This research was carried out in the nursery of Tishreen University and the laboratories of the Faculty of Agriculture to determine the suitable duration of stratification at a temperature of 5 ° C sprouting for seeds of several varieties of pistachios (“Abu Raiha”, “Ajami” and “Marawhi”), and raise their germination rate. The results show that: • The Germination speed of seed treated with wet stratification at a temperature of (5 ° C ± 2 ° C) differed from one variety to another and were as follows: • The treatment of seeds stratification process for 45 days at a temperature of 5 ° C increased the speediness of seeds germination of the studied varieties "Abu Raiha", "Ajami" and "Marwahi", and it was the best compared to other treatments, where the germination speed reached (3.03 days, 13.41 days, 12.05 days), respectively Followed by the stratification treatment for 30 days (4.90 days, 23.11 days, 18.64 days) compared to the control, which required (97.53, 73.53 and 41.76 days) for germination of 50% of the seeds. This is confirmed by the results of the statistical analysis. -Also the stratification treatment for a duration of 45 days before planting gave the highest germination rate of seeds of the two cultivars "Abu Raiha" and "Ajami" (94.79% and 71.87%), respectively, while the treatment for 30 days gave the seeds of the variety "Marawhi" the highest germination rate ( 86.46%), followed by the treatment of stratification for a duration of 45 days (79.69%) without significant differences between them, while the percentage of germination in the control was (30.21, 36.15% and 23.96%) for each of the varieties "Abu Raiha", "Ajami" and "Marawhi", respectively. Consequently, the results of the statistical analysis confirmed the superiority of the two treatments of stratification for 45 days and 30 days over the rest of the other treatments.